Peribahasa Urang Banjar Perspektif Islam dalam Menangkal Hoax dan Ujaran Kebencian di Media Sosial - Muhammad Hafidz Ilmi (Alhadharah: Jurnal Ilmu Dakwah, 2021)
The recent outbreak of hoaxes and hate speech on social media is very concerning. Through a medium, various opinions are easily expressed. But what is unfortunate is that this freedom is not accompanied by knowledge in its use, so negative impacts such as hoaxes or fake news and hate speech quickly spread everywhere. Therefore, this study aims to provide answers related to this problem. Through the local wisdom of the Banjar people in the form of proverbs that have been taught for generations. They turn out to contain Islamic principles that can be used in communication, especially in countering hoaxes and hate speech on social media, such as the principle of qaulan sadida, tawakkuf, speaking well or silent, tabayyun, and the principle of iqra or revitalizing literacy culture. The purpose of writing this article is to find out what causes hoaxes and hate speech to spread quickly and how the role of the Banjarese proverb from an Islamic perspective in counteracting hoaxes and hate speech on social media. The writing method applied in this article is library research from various sources and with a qualitative descriptive approach